Education for Sustainable Development as the Catalyst for Local Transitions Toward the Sustainable Development Goals - Kioupi, Vasiliki; Voulvoulis, Nikolaos (Frontiers in Sustainability, 2022)
Education for Sustainable Development (ESD) is hypothesized to enable the transition to a sustainable future as envisioned by the UN Sustainable Development Goals (SDGs). To demonstrate the potential of ESD to facilitate such a transition, research was carried out between 2018 and 2020, using a systems thinking approach to enable educational communities develop their own visions around the SDGs through a participatory process of localisation of sustainability goals and targets and an alignment with formal educational outcomes. Three case studies implemented in a University and two Schools in the UK where evaluated as to their capacity to facilitate these transitions through the development of sustainability competences in their learners. Findings from the application of the systemic framework for transitions towards the SDGs through ESD and assessment tools for sustainability competence attainment in learners are discussed in depth. Important barriers and enablers of the process are identified, as well as leverage points to increase the effectiveness of interventions. This work aims to inform education practitioners and community stakeholders about the potential of ESD and practices they can adapt to their own needs and circumstances.